Penerapan Metode Kerja Kelompok dan Media Gambar untuk Meningkatkan Hasil Belajar Tematik Siswa di SD Negeri 2 Tete - Jaurah, Jaurah (Jurnal Paedagogy, 2021)
This study aims to improve students' thematic learning outcomes through the use of group work methods and image media. This study uses a classroom action research method. The subjects of this study were 23 students of class III SD Negeri 2 Tete. Data collection techniques using tests and observation sheets. Meanwhile, the data analysis technique used in this research was quantitative and qualitative descriptive analysis. Based on the results of the research that has been carried out, it can be concluded that students become more enthusiastic and motivated in thematic learning, data from cycle to cycle shows that student learning outcomes have increased. From 21.74% of students who completed to 56.52% in cycle 1, then in cycle 2 increased to 100%. Through the application of group work methods and image media in thematic learning can improve learning outcomes of grade III even semester SD Negeri 2 Tete with a 100% completeness percentage.